(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
It has been observed that the English language as spoken in Nigeria (even among educated speakers) differ remarkably from that spoken by speakers of inner circle English. Consequently, this paper, from a graphophonemic perspective, examines how speakers of Educated Nigerian English accent (ENEA) phonemically represent six vowel graphemes <ia, ie, io, iou, eo, and eou> appearing in an unstressed final syllable having a palato-alveolar-realizing consonant grapheme as its onset. Using ninety-six lexical items gathered from a word database and via a purposive sampling technique, the study tries to determine if the phonemic realizations of these graphemes in ENEA differ from those of British RP. Sixty final year undergraduate students were randomly selected, from two federal universities, and they cut across speakers from six geopolitical zones in Nigeria. Their pronunciation of the ninety-six words were recorded, played and analyzed as perceived, using Taxonomic Phonology as the theoretical framework. It is found that while all the graphemes are realized as schwa sound in British RP, there are about six variants in ENEA resulting from the type of vowel letters representing the graphemes. The paper then concludes that phonemic realizations of graphemes in ENEA are usually influenced by overgeneralization of the default sounds of the graphemes. Hence, the study recommends a graphophonemic approach in studying phonemic features of ENEA.